Carotenoid composition of Brazilian fruits and vegetables - Rodriguez-Amaya, D. B.; Amaya-Farfan, J.; Kimura, M. [UNESP] (My University, 2007)
Brazil has a wide diversity of food sources of carotenoids. The updated Brazilian database consists of more than 270 items of fruits, vegetables and their prepared and processed products. The database demonstrates variations due to variety, maturity, production technique, climate and processing. Many of these foods are not found in the US and European databases. Good to rich sources (>20 μg/g) of β-carotene are: acerola, bocaiúva, mango 'Extreme' and tucumã. Sources of both α-carotene and β-carotene are buriti, carrot, Cucurbita moschata 'Menina Brasileira', 'Baianinha' and 'Goianinha', and red palm oil. Commercially produced and uncultivated or semi-cultivated leafy vegetables, C. maxima 'Jerimum Caboclo' and the hybrid Tetsukabuto, cooked broccoli are sources of lutein and β-carotene. The edible Tropaeolum majus flower is especially rich in lutein. Although many fruits have β-cryptoxanthin as principal carotenoid (e.g. caja, nectarine, peach, orange-fleshed papaya, tree tomato), the levels are below 20 μg/g. Good to rich sources of lycopene are guava and guava products, papaya, pitanga and pitanga juice, tomato and tomato products, and watermelon. Sources of zeaxanthin are rare; although the principal carotenoid of piqui, the amount is low, lower than that found in buriti.
Keywords: α-carotene; β-carotene; β-cryptoxanthin; Food sources; Lutein; Lycopene; Zeaxanthin; Brassica oleracea var. italica; Carica papaya; Citrullus lanatus var. lanatus; Cucurbita moschata; Daucus carota; Eugenia uniflora; Lycopersicon esculentum; Prunus persica; Prunus persica nucipersica; Psidium; Solanum betaceum; Tropaeolaceae; Tropaeolum majus